2021
DOI: 10.1021/acsaem.1c01292
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Feasibility of Manganese Substitution for Cobalt in the Synthesis of Nickel-Rich and Cobalt-Free Cathode Materials

Abstract: LiNi 0.8 Co 0.15 Al 0.05 O 2 (LNCA) cathode materials have an extremely high energy density, which can greatly enhance the driving range of pure electric vehicles if they are used in onboard batteries. However, the development of the LNCA cathode material is restricted by the expensive transition metal cobalt (Co). Therefore, researchers are devoted to finding other metals to replace Co to synthesize nickel (Ni)-rich Co-free materials to reduce the cost. To investigate the feasibility of replacing Co with mang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
(86 reference statements)
0
7
0
Order By: Relevance
“…5l, which were obtained according to the GCD curves of NiCo-MOF-2//AC. Impressively, the NiCo-MOF-2-based SSSC achieved a maximum energy density of 0.65 mW h cm −2 at a power density of 2 mW cm −2 , which is superior to other reported devices, such as NC LDH NSs@Ag@ CC//AC (40 μW h cm −2 at 12.1 mW cm −2 ), 64 Co(OH) 2 /CoOOH/Co 3 O 4 /Cu(OH) 2 //AC (196.1 μW h cm −2 at 1.6 mW cm −2 ), 65 Co 3 O 4 @NiMoO 4 //AC(0.17 mW h cm −2 at 16 mW cm −2 ), 66 Co-MOF/NF//AC (210 μW h cm −2 at 3761.2 μW cm −2 ), 67 NiCo-LDH//AC (31.1 μW h cm −2 at 3.5 mW cm −2 ), 68 Ni 1 Co 2 Al-LDHs@CC//AC (0.102 mW h cm −2 at 0.75 mW cm −2 ), 69 NiO/Ni(OH) 2 /PEDOT//CW/CMK (0.01 mW h cm −2 at 0.33 mW cm −2 ), 70 as well as close to the Co-MOF@NiCo-LDH//AC (0.89 mW h cm −2 at 7.5 mW cm −2 ), 71 and NiCo-NH 2 -BDC-MOF NS/NF//AC (0.81 mW h cm −2 at 1.6 mW cm −2 ) 72 based devices.…”
Section: Resultsmentioning
confidence: 99%
“…5l, which were obtained according to the GCD curves of NiCo-MOF-2//AC. Impressively, the NiCo-MOF-2-based SSSC achieved a maximum energy density of 0.65 mW h cm −2 at a power density of 2 mW cm −2 , which is superior to other reported devices, such as NC LDH NSs@Ag@ CC//AC (40 μW h cm −2 at 12.1 mW cm −2 ), 64 Co(OH) 2 /CoOOH/Co 3 O 4 /Cu(OH) 2 //AC (196.1 μW h cm −2 at 1.6 mW cm −2 ), 65 Co 3 O 4 @NiMoO 4 //AC(0.17 mW h cm −2 at 16 mW cm −2 ), 66 Co-MOF/NF//AC (210 μW h cm −2 at 3761.2 μW cm −2 ), 67 NiCo-LDH//AC (31.1 μW h cm −2 at 3.5 mW cm −2 ), 68 Ni 1 Co 2 Al-LDHs@CC//AC (0.102 mW h cm −2 at 0.75 mW cm −2 ), 69 NiO/Ni(OH) 2 /PEDOT//CW/CMK (0.01 mW h cm −2 at 0.33 mW cm −2 ), 70 as well as close to the Co-MOF@NiCo-LDH//AC (0.89 mW h cm −2 at 7.5 mW cm −2 ), 71 and NiCo-NH 2 -BDC-MOF NS/NF//AC (0.81 mW h cm −2 at 1.6 mW cm −2 ) 72 based devices.…”
Section: Resultsmentioning
confidence: 99%
“…After reacting for 40 h, the feed was stopped and aged for 30 min. Finally, after filtration, washing, and drying, Ni-rich quaternary precursors with different Co and Mn contents were obtained …”
Section: Methodsmentioning
confidence: 99%
“…Hence, they will largely inhibit Li/Ni disorder and enhance the reversible lithium de/intercalation, thereby improving the original electrochemical performance. 60 However, Li et al recently reported that the efficacy of Co in high-Ni layered oxides is not good as other dopants (such as Mg, Mn, and Al). 61 Similar amounts of Ni 2+ disorder can be obtained when the LNO is substituted with 5% Mg, Al, and Co, implying that Co cannot achieve an extra reduction of cation mixing.…”
Section: Methodsmentioning
confidence: 99%
“…According to the previously mentioned magnetic frustration theory, Co 3+ ions do not have a magnetic moment and can help relieve the magnetic frustration in the transition metal layer. Hence, they will largely inhibit Li/Ni disorder and enhance the reversible lithium de/intercalation, thereby improving the original electrochemical performance …”
Section: Anatomy Of Co Effectiveness In Ni-rich Materialsmentioning
confidence: 99%